2020
DOI: 10.3389/fphys.2020.563981
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Organoids as Disease Models: Strengths, Weaknesses and Perspectives

Abstract: Chronic kidney disease is a major global health problem, as it affects 10% of the global population and kills millions of patients every year. It is therefore of the utmost importance to develop models that can help us to understand the pathogenesis of CKD and improve our therapeutic strategies. The discovery of human induced pluripotent stem cells (hiPSCs) and, more recently, the development of methods for the generation of 3D organoids, have opened the way for modeling human kidney development and disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 54 publications
(116 reference statements)
0
25
0
Order By: Relevance
“…Despite the developmental limitations with iPSC-derived kidney organoids, including lack of directional cues, vascularization, and cortical-medullary segmentation (Romero-Guevara et al, 2020), this system has morphological and molecular features comparable to fetal kidney tissue that overcome species differences and provides a complex in vitro environment to examine BM assembly (Bantounas et al, 2018). We demonstrated that kidney organoids differentiate into glomerular structures containing the cells required for GBM assembly and single-cell transcriptomic studies have also shown over 20 other distinct cell populations in kidney organoids (Combes et al, 2019a;Wu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the developmental limitations with iPSC-derived kidney organoids, including lack of directional cues, vascularization, and cortical-medullary segmentation (Romero-Guevara et al, 2020), this system has morphological and molecular features comparable to fetal kidney tissue that overcome species differences and provides a complex in vitro environment to examine BM assembly (Bantounas et al, 2018). We demonstrated that kidney organoids differentiate into glomerular structures containing the cells required for GBM assembly and single-cell transcriptomic studies have also shown over 20 other distinct cell populations in kidney organoids (Combes et al, 2019a;Wu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Co-culture techniques have been successfully applied to mimic specific tissues. In 2011, Slater et al used the co-culturing method to generate a functional tri-layer in vitro model of the glomerular filtration barrier, comprising podocytes and glomerular epithelial cells on an artificial membrane [118].…”
Section: D Versus 3d Modelsmentioning
confidence: 99%
“…Besides improving rodent models, the establishment of pluripotent stem-cell-based kidney cells in 2D or 3D organoids holds great potential for gaining further insights into disease mechanisms and potential therapies [ 12 ]. Recent studies have suggested using primary kidney cells for the generation of kidney organoids as an alternative to pluripotent stem cells [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%